Rationally Designed Pentapeptide Analogs of Aβ19–23 Fragment as Potent Inhibitors of Aβ42 Aggregation - Sachin B. Baravkar; Yan Lu; Qi Zhao; Hongying Peng; Weilie Zhou; Song Hong (Molecules)
Amyloid beta (Aβ42 and Aβ40) aggregation, along with neurofibrillary tangles, is one of the major neurotoxic events responsible for the onset of Alzheimer’s disease. Many potent peptide-based inhibitors mainly focusing on central hydrophobic core Aβ16–20 (KLVFF) have been reported in recent years. Herein, we report pentapeptides 1–4, based on the β-turn-inducing fragment Aβ19–23 (FFAED). The synthesis of peptides 1–4 was carried out using Fmoc/tBu-based solid-phase peptide synthesis technique, and it was found that pentapeptide 3 potently inhibit the aggregation propensity of Aβ42, when incubated with it at 37 °C for 48 h. The aggregation inhibition study was conducted using thioflavin T-based fluorescence assay and circular dichroism spectroscopy, and supported by transmission electron microscope imaging. The conformational change on the aggregation of Aβ42 and aggregation inhibition by peptides 1–4 was further evaluated using 1H–15N HSQC NMR spectroscopy. The results demonstrated that the most potent analog, peptide 3, effectively disrupts the aggregation process. This study is the first to demonstrate that an Aβ19–23 fragment mimic can disrupt the aggregation propensity of Aβ42.